PFD-SENTINEL: Development of a screening tool for pelvic floor dysfunction in female athletes through an international Delphi consensus - Giagio, S.; Salvioli, S.; Innocenti, T.; Gava, G.; Vecchiato, M.; Pillastrini, P.; Turolla, A. (British Journal of Sports Medicine, 2023)
To develop a screening tool for pelvic floor dysfunction (PFD) in female athletes for use by sports medicine clinicians (eg, musculoskeletal/sports physiotherapists, sports and exercise medicine physicians), which guides referral to a PFD specialist (eg, pelvic floor/women`s health physiotherapist, gynaecologist, urogynaecologist, urologist).